SOIL SURFACE CRUST: ITS SIGNIFICANCE, TYPES AND MECHANICS OF FORMATION. A REVIEW - yousif alnaser; Qahtan Alkhafagi (Mesopotamia Journal of Agriculture)
Most of the agricultural soils around the world suffer from increased soil degradation and erosion and reduce moisture conservation, which is the decisive factor in agricultural crop production, and among these problems is the phenomenon of Surface Soil Crusting (SSC), which is spread in a wide range of climates, especially in dry and semi-arid soils. In this review, the focus was done on the significance of SSC, its formation mechanisms, stages of emergence, types of crusts, methods used to estimate crust hardness and its resistance to penetration. It was noted that SSCs are formed when raindrop falls on newly plowed soils or soils without vegetation, followed by periods of drought, thus destroying soil aggregates and splashing there fine particles, these particles enter the inter-pores, Leading to formation of hard thin layers at the soil surface with thickness ranges from several millimeters to several centimeters or these particles moved by surface runoff water to deposit in the bottom of valleys, forming a sedimentary crust of five to seven centimeters thick. The SSC are generally divided into three main parts, namely, structural crusts, sedimentional crusts, in addition to the Biological soil crusts, which is formed over the previous two types and consists of fungi, algae, lichens and bacteria. Crust hardness can be measured or estimated by two main methods, which are Modulus of Rupture, and crust Penetration Resistance.